Determination of cellulase and protease activity of fungi isolated from wood decay - Ahmad Fazilah, Nasha Allysha (2015)
In nature, organic substances are found either as simple carbon or nitrogen molecules are found as complex polymers of these simple molecules. These substances may be of plant, animal or microbial origin. Simple organic molecules are utilized by the living organisms and get converted into cellular materials and finally enter into the mineral cycling. Substances such as starch, celluloses, hemicelluloses, proteins, fats and oils, pectin, lignin are the major complex organic substances and many of these are quite resistant to enzyme degradation. However, certain microorganisms produce enzymes that can hydrolyze such molecules into simple substances. Certain fungi for example, wood decay fungi are able to hydrolyze cellulose and protein. This study was aimed to observe the potential of particular wood decay fungi as a new source for cellulase and protease enzyme. There are a lot of fungal species that have not recorded yet. Comparison of the cellulolytic activity and the proteolytic activity between four isolates C1 and C2 (cellulolytic fungi) and P1 and P2 (proteolytic fungi) was done by studying the cellulolytic and proteolytic activity of the isolates. The cellulase activity for isolates C1 and C2 were 0.0017 and 0.00094 respectively, while the protease activity for isolates P1 and P2 were 0.1462 and 0.251 respectively. Isolate C1 was found to have the highest activity in cellulase assay and isolate P2 was found to have highest protease activity compare to isolate P2 in protease assay. From the microscopic identification, isolate C1 was assumed to be Aspergillus niger while other isolates cannot be identified. Thus, further research, such as molecular identification, for example, amplification using PCR and sequencing of 18S rDNA of the isolates are suggested.